Detection of Some Virulence Factors, Antibiotics Resistant and esp Gene Expression in Enterococcus faecalis bacteria - Karim, Farah Mohammed; Alshwaikh, Rana Mujahid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study aimed to identify virulence factors in Enterococcus faecalis and investigate theexpression of the esp gene responsible for biofilm formation. Seventy isolates of E. faecaliswere collected from various clinical specimens, including urine, stool, wound swabs, anduterine secretions, from several hospitals and laboratories in Baghdad, such as the CentralChild Teaching Hospital, Baghdad Teaching Hospital, and the National Center forEducational Laboratories, during the period from 1 July 2022 to 1 September 2022. Allisolates were confirmed as E. faecalis through microscopic examination, biochemical tests,and the VITEK 2 system. The virulence factors investigated were haemolysin, gelatinase, andbiofilm formation. The results showed that 53.12% of isolates exhibited β-haemolysis,90.62% were capable of forming biofilms, and 65.62% produced the enzyme gelatinase.Antibiotic susceptibility testing using the VITEK 2 system revealed that all isolates weresensitive to linezolid, teicoplanin, vancomycin, and tigecycline, while they showed 100%resistance to erythromycin. Sensitivity to other antibiotics varied among isolates. Expressionof the esp gene, associated with biofilm formation, was analysed using real-time PCR basedon the SYBR Green method, with 16S rRNA as a housekeeping control gene. When theisolates were treated with erythromycin at concentrations of 0.8 mg/L and 1.6 mg/L, nosignificant increase in esp gene expression was observed. In conclusion, E. faecalis isolatesfrom various clinical sources in Baghdad exhibited several virulence factors, includinghaemolysin, gelatinase, and strong biofilm-forming ability. The isolates showed completeresistance to erythromycin while remaining sensitive to several other antibiotics, andtreatment with erythromycin did not enhance esp gene expression.